A topical approach to life span development - Santrock, John W. (Boston : McGraw Hill, 2007)
Contenido: The life span perspective. Biological beginnings. Biological processes, physical development, and health. Physical development and biological aging. Health. Motor, sensory and perceptual development. Cognitive developmental. Information processing. Cognitive processes and development. Intelligence. Language development. Emotional development. Socio emotional processes and development. The self, identity and personality. Gender and sexuality. Moral development, values and religion. Families, lifestyles, and parenting. Peers and the sociocultural world. Schools, achievement and work- Death and grieving.